TRANSITIVITY SYSTEM IN READING PASSAGE OF ENGLISH TEXTBOOK FOR JUNIOR HIGH SCHOOL - Arifiani, Fathur Rizqi; -, Meisuri - (Universitas Negeri Medan, 2014)
ABSTRACT This study is concerned with transitivity system used in reading passage for junior high school. The objectives of this research were to find out the process type of transitivity system, the most dominant process type and to describe the implication of the most dominant process type used in Reading Passage of English Textbook for Junior High School. This study was conducted by using descriptive qualitative design. There were six types of process in 182 clauses. The result of data analysis showed that the numbers in types of process were: material (45,1%), mental (16,5%), relational (26,9%), behavioral (2,7%), verbal (7,7%), and existential (1,1%). The most dominant process type used is Material process. That means that many reading passages in English textbook for junior high school contain action, or happened physicaly. So the process used in reading passages indicated action, doing things or what is done. Keywords: types of process, reading passage